Intermediate algebra: Alternate approach - Charles P McKeague (Saunders College, 1993)
The book is divided into 10 chapters. Chapter 1 reviews real numbers, exponents, and polynomials. Chapter 2 deals with sequence and variety of topics. Chapter 3 presents linear equations and inequalities, parabolas, and inverse variation. Chapter 4 deals with simple rational functions. Chapter 5 introduces square and cube root equations. Chapter 6 presents parabolas. Chapter 7 covers systems of equations. Chapter 8 presents conic sections, cubic and exponential functions. Chapter 9 presents logarithmic functions. Chapter 10 deals with sequences and series in general and their specific categories